Detection of subsurface basaltic sheets and associated structures utilising forward modelling and inversion of 2D electrical resistivity data: A case study from Jebel-Qatrani, Fayoum, Egypt - Muhammad A. EL HAMEEDY; Walid M. MABROUK; Said DAHROUG; Ahmed M. METWALLY (Contributions to Geophysics and Geodesy, 2023)
In the north of Fayoum Governate, Egypt, numerous extrusive flows of basalt rocks exposed on the surface and affected by weathering and erosion, forming altered basalt sheets which is the case of the Jebel-Qatrani. The study objective comes in two main folds: the first, to choose the optimum parameters required for the filed survey by generating forward models using several arrays with 3% Gaussian random noise, simulating the geology of the study area deploying a finite element modelling approach; the second, to acquire the real field data and generate the electrical resistivity tomograms to ascertain the existence, extension, and characteristics of the basaltic sheets in the subsurface. Hence, four electrical resistivity profiles with a Wenner-alpha array with 48 electrodes, 5 metre electrode spacing, and a total length of 235 metres were acquired in suitable locations based on previous aeromagnetic results in the vicinity of the study area. These profiles were inverted to derive the true resistivity distribution of the subsurface. Another objective is to detect the near-surface, Oligocene normal faulting structures associated with rifting of the Red Sea. Results from two inverted resistivity tomograms show a possible normal fault cutting through the early Oligocene Qatrani Formation at the same time as red sea rifting, confirming previous geological studies in the Fayoum region based on satellite imagery, aeromagnetic data, and geological outcrops. It is concluded that near these faults, a sheet-like body of relatively high resistivity values, representing basaltic extrusions, was detected, confirming that the basaltic presence is associated with these structural zones.